Emergence of the aphid Hysteroneura setariae (Thomas, 1878) and ladybird predators Coccinella septempunctata L., 1758 (Coleoptera: Coccinellidae) on the grass Muhlenbergia capillaris (Lamark) Trinius in central Japan - Yamazaki, Kazuo (Entomological Communications, 2023)
Pink muhly grass Muhlenbergia capillaris (Lamark) Trinius is a perennial, tussock-forming grass that is native to North and Central America. The reddish-purple coloration of the spikes of this species has resulted in this grass becoming popular as an ornamental plant around the world. Interestingly, very few insects have been reported to be associated with this grass. I therefore examined arthropod assemblages on M. capillaris in two urban parks in central Japan in autumn and found that the aphid Hysteroneura setariae (Thomas, 1878) (Hemiptera: Aphididae) and its natural ladybird predator Coccinella septempunctata L., 1758 (Coleoptera: Coccinellidae) occurred at high densities at one of the parks (ca. 9000 vs 3.4 individuals/m2). Other insect pests, such as the moth Helicoverpa armigera (Hübner, 1808) (Lepidoptera: Noctuidae) and mirid bugs were also present, but at markedly lower densities. Since H. setariae is not a pest in Japan and C. septempunctata is a beneficial predator, M. capillaris could be used as a banker plant in agricultural fields as well as in urban green spaces.